HUKUM MELAKUKAN PENIMBUNAN HARTA/MONOPOLI (IHTIKÂR) DALAM PERSPEKTIF HADIS - Sukiati Sukiati (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2009)
Abstract: The Legal Position of Monopoly (ihtikâr ) in Hadîts Perspectives. One of the functions of prophetic traditions (hadîts) is to provide explanation for the Qur’anic injunctions. In line with this function, no single verse did the Qur’an deal with the issue of monopoly. Monopoly is a kind of social dealing or trading that causes the society suffer at the most. The merchant hoards certain goods and monopolizes the market when the supply decreases while the demand raises, and when social demand reaches its peak, the merchat releases the goods and sells them in very high prices. Through close reading of the prophetic tradition, the author argues that there can be found some tenets which expressedly prohibit such practice. This essay attempts to examine the validity of monopoly related prophetic traditions and concludes that their validity can be achieved.Kata Kunci: ihtikâr, takhrîj, ekonomi Islam